Inovasi Pelayanan Publik E-KTP Keliling Di Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Sumbawa - Sagita, Suci Syafti Sagita; Saleh, Amin; Dermawan, M Ariy (Jurnal Administrasi Publik dan Pemerintahan, 2025)
Public service innovation has become a strategic step to enhance the quality and reach of government services, particularly in the field of population administration. This study examines the E-KTP Mobile Service innovation through the Jago Desa program implemented by the Department of Population and Civil Registration of Sumbawa Regency, aimed at addressing geographical challenges and the low accessibility of population documents. The purpose of this research is to analyze the effectiveness, sustainability, as well as supporting and inhibiting factors of the program's implementation. This study employs a descriptive qualitative approach with data collected through observation, in-depth interviews, and documentation. The findings show that Jago Desa is effective in directly reaching communities through a proactive service model (stelsel aktif), supported by two dedicated service teams. The uniqueness of this program lies in its culturally rooted naming and integrated on-site printing services, which had never been implemented before. It has positively impacted the increase in E-KTP coverage, the validity of population data, and public satisfaction with civil registration services. The program also demonstrates high replication potential, supported by repeated requests from local governments and its alignment with national innovation policies. Despite challenges such as limited operational facilities and difficult geographical conditions, Jago Desa is overall recognized as an effective, adaptive, and sustainable public service innovation